2013
DOI: 10.1148/radiol.12112707
|View full text |Cite
|
Sign up to set email alerts
|

Filtered Back Projection, Adaptive Statistical Iterative Reconstruction, and a Model-based Iterative Reconstruction in Abdominal CT: An Experimental Clinical Study

Abstract: The MBIR algorithm considerably improved objective and subjective image quality parameters of routine abdominal multidetector CT images compared with those of ASIR and FBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(112 citation statements)
references
References 30 publications
7
105
0
Order By: Relevance
“…These include iterative reconstruction models such as adaptive statistical iterative reconstruction and model-based iterative reconstruction. [9][10][11][12][13][14][32][33][34][35][36][37][38][39][40] Although these imaging algorithms provide an additional method for dose reduction in CT-guided procedures, their availability is currently limited to newer CT scanners for routine diagnostic CT imaging. The greater availability of the iterative reconstruction software over time may allow for increased operator comfort when evaluating low-dose images during CT-guided procedures, potentially further reducing the radiation dose.…”
Section: Discussionmentioning
confidence: 99%
“…These include iterative reconstruction models such as adaptive statistical iterative reconstruction and model-based iterative reconstruction. [9][10][11][12][13][14][32][33][34][35][36][37][38][39][40] Although these imaging algorithms provide an additional method for dose reduction in CT-guided procedures, their availability is currently limited to newer CT scanners for routine diagnostic CT imaging. The greater availability of the iterative reconstruction software over time may allow for increased operator comfort when evaluating low-dose images during CT-guided procedures, potentially further reducing the radiation dose.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MBIR can be applied in only one strength, whereas previous iterative techniques could be applied in gradations (eg, 30% adaptive statistical iterative reconstruction [ASIR] combined with filtered back projection [FBP]). To date, only a few studies in which researchers evaluated the effect of MBIR on patient radiation dose and image quality have been published (14)(15)(16)(17)(18). Such studies, mostly in adults, have shown that MBIR leads to substantial dose reductions but maintains diagnostic image quality and reduces image noise.…”
Section: Methodsmentioning
confidence: 99%
“…It is not clear what the effect on measurement error would be for non-spherical nodules at these sizes and densities, or for CT scans reconstructed using iterative reconstruction (IR) algorithms, which have re-emerged in clinical scanners as part of the ongoing effort to reduce patient radiation exposure while maintaining image quality (19,20). Different types of IR include adaptive (or statistical as they are sometimes referred to) algorithms, which use predictor models of statistical noise in iterative procedures to reduce noise on FBP reconstructed scans, and model-based algorithms which incorporate more complex system models of data statistics, X-ray physics, and system optics in the image reconstruction process (21). Additionally, it would be beneficial to quantify the interrelated effects of nonsolid nodule characteristics (size, shape, density) and reconstruction algorithm with a wide range of dose levels to determine any reductions in exposure that can be achieved while still maintaining measurement consistency.…”
Section: Introductionmentioning
confidence: 99%